2011
DOI: 10.1177/0018720811425043
|View full text |Cite
|
Sign up to set email alerts
|

Continuously Informing Vibrotactile Displays in Support of Attention Management and Multitasking in Anesthesiology

Abstract: This study can inform display design to support multitasking performance of anesthesiologists in the clinical setting and other supervisory control operators in work domains characterized by high demands for visual and auditory resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 30 publications
(44 reference statements)
4
81
0
Order By: Relevance
“…Our results from the tactile feedback tasks are consistent with previous work in anesthesia and rehabilitation that found the tactile modality can be used to unobtrusively provide feedback to anesthetists and improve and postural control without reducing performance [10]. This work is limited to surgical simulation tasks and will need to be tested in the field (surgical training and practice settings) in order to fully understand the potential of this technology.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results from the tactile feedback tasks are consistent with previous work in anesthesia and rehabilitation that found the tactile modality can be used to unobtrusively provide feedback to anesthetists and improve and postural control without reducing performance [10]. This work is limited to surgical simulation tasks and will need to be tested in the field (surgical training and practice settings) in order to fully understand the potential of this technology.…”
Section: Discussionsupporting
confidence: 85%
“…Training in good ergonomic practices such as improved upper body posture could prevent poor musculoskeletal health habits. Since a vibrotactile feedback modality has been successful in improving performance in healthcare [10] and this study has not indicated significant performance decrement, this feedback method can be pursued for surgical team member posture training. Continued research is needed for feedback that is joband task-specific for preventing musculoskeletal disorders.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent studies have designed a particular class of tactile signals, called tactile icons or tactons, that constitute a form of structured abstract messaging that can potentially convey meaningful information by simultaneously manipulating one or several of the parameters of tactile cues (such as vibration frequency, duration, intensity, waveform and location; see, Brewster and Brown, 2004;Jones and Sarter, 2008;Jones et al, 2009;Ferris and Sarter, 2011). In fact, some of the earliest attempts to communicate meaningful information via the skin surface can be traced back to Geldard (1957)'s seminal early work, where the first tactile language called "Vibratese" was designed (for conditions of passive stimulation).…”
Section: Meaningful Tactile Warning Signalsmentioning
confidence: 99%
“…Also, in the case of the sound situation at the NICU, investigations only focus on certain fields of research. Investigations are either narrow, example is Ferris and Sarter (2011) who test a prototype -or the investigations are broad, example is Edworthy (2000) on the ergonomics of sound. But no study brings together the whole scope of selected issues that need to be considered regarding nurses' work, and infant's health, development and well-being and how they relate to each other.…”
Section: Designing For Human-tech Levelsmentioning
confidence: 99%